Zu Besonderheiten des Österreichischen aus Sicht eines Auslandsgermanisten - Lewandowski, Andrzej (Glottodidactica, 2000)
The main aim of the article is creating a basis for application of the most typical vocabulary for the area of Austria in teaching materials for German students. In the article there is a short analysis of the most common words of Austrian origin in everyday life, their etymology, peculiarity and typical lexical and phonetic differences between German and Austrian. The analyzed examples were taken from Austrian press and popular Austrian dictionaries.